Comparison of biochemical, microbial and mucosal mRNA expression in bile acid diarrhoea and irritable bowel syndrome with diarrhoea. Issue 1 (17th May 2022) - Camilleri, Michael; Carlson, Paula; BouSaba, Joelle; McKinzie, Sanna; Vijayvargiya, Priya; Magnus, Yorick; Sannaa, Wassel; Wang, Xiao Jing; Chedid, Victor; Zheng, Ting; Maselli, Daniel; Atieh, Jessica; et al.
Abstract : Objective: There are altered mucosal functions in irritable bowel syndrome with diarrhoea (IBS-D); ~30% of patients with IBS-D have abnormal bile acid (BA) metabolism (ABAM) and diarrhoea (summarised as BAD). Aim: To compare biochemical parameters, gastrointestinal and colonic transit, rectal sensation and pathobiological mechanisms in IBS-D without ABAM and in BAD (serum 7C4>52 ng/mL). Design: In patients with Rome III criteria of IBS-D, we compared biochemical features, colonic transit, rectal sensation, deep genotype of five BA-related genes, ileal and colonic mucosal mRNA (differential expression (DE) analysis) and stool dysbiosis (including functional analysis of microbiome). Results in BAD were compared with IBS-D without ABAM. Results: Compared with 161 patients with IBS-D without ABAM, 44 patients with BAD had significantly faster colonic transit, lower microbial alpha diversity, different compositional profile (beta diversity) and higher Firmicutes to Bacteroidetes ratio with evidence of decreased expression of bile acid thiol ligase (involved in transformation of primary to secondary BAs) and decreased sulfatases. In BAD (compared with IBS-D without ABAM), terminal ileal biopsies showed downregulation of SLC44A5 (a BA transporter), and ascending colon biopsies showed upregulation in barrier-weakening genes ( CLDN2 ), serine protease inhibitors, immune activation, cellular differentiation and a cellular transporter ( FABP6 ; BA binding). No DE of genes was documented in descending colon biopsies. The two groups had similar rectal sensation. Conclusion: Though sharing clinical symptoms with IBS-D, BAD is associated with biological differences and mechanisms that have potential to enhance diagnosis and treatment targeting barrier dysfunction, inflammatory and microbial changes.